Molecular detection of acute lymphoblastic leukaemia in boys with testicular relapse. Issue 5 (October 1998) - Lal, A; Kwan, E; al Mahr, M; Zhou, L; Ferrara, D; Tobias, V; O'Gorman Hughes, D; Haber, M; Norris, M D; Marshall, G M
Abstract : AIMS: To determine the role of polymerase chain reaction (PCR) based minimal residual disease (MRD) detection of leukaemia specific DNA in testicular relapse in childhood acute lymphoblastic leukaemia. METHODS: DNA was obtained from archival testicular and bone marrow samples from boys with acute lymphoblastic leukaemia who relapsed in the testes. Overlapping DJH clone specific primers derived from clonal immunoglobulin heavy chain (IgH) gene rearrangement in each case were used to analyse testicular or bone marrow DNA. RESULTS: Histologically normal end of treatment testicular biopsies in the five patients in longterm remission were all MRD negative, but MRD positive in three of six boys with subsequent testicular relapse. Histologically normal bone marrow samples taken at the end of treatment were MRD negative in five of seven cases, but MRD positive in all cases at the time of isolated testicular relapse. Three boys with unilateral testicular relapse underwent unilateral orchidectomy, rather than bilateral testicular irradiation, as part of their treatment. Two of these boys were MRD positive in the histologically uninvolved testes, and both had subsequent relapses either in the testes or the bone marrow, while the MRD negative patient has not had a testicular relapse. CONCLUSIONS: The presence of MRD in testicular tissue can be assayed with a PCR based method to detect clone specific antigen receptor gene rearrangements. In this setting, PCR is more sensitive than conventional testicular histology for predicting clinical outcomes. MRD assays might be useful in the management of boys at the time of isolated testicular relapse, to confirm the presence of unilateral testicular disease.